African Union Great Green Wall Initiative Experts’ and Partners’ Engagement Meeting: Transformative Collaboration for African Land Restoration - Africa Union; Accelerating Impacts of CGIAR Climate Research for Africa (2025)
This concept note presents the context, objectives and expected outcomes for the African Union (AU) Great Green Wall Initiative (GGWI) Experts’ and Partners’ Engagement Meeting which was held from the 13th - 15th May 2025 at the AU Headquarters in Addis Ababa, Ethiopia. The concept note gives an overview of the AU GGWI Strategy and Ten-Year Year Implementation Framework (2024-2034). It provides a background to the evolution of the GGWI, its progress and challenges, and areas for improvement and prioritised action. It outlines the strategic framework of the GGWI Strategy, highlighting the four intervention axes and noting the proposed way forward for operationalisation.